NEGOTIATING IDENTITY AND AUTHORITY THROUGH CODE-MIXING IN SARA WIJAYANTO’S MYSTICAL YOUTUBE - Dini Arifa Ayunisa (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The phenomenon of code-mixing in digital mystical content demonstrates a shift in the role of language from a communication tool to a technique for establishing spiritual authority and social legitimacy. Although there has been a lot of research on code-mixing in education, entertainment, and general media, there have been few studies that emphasize this technique in the world of digital mysticism. This research will look at how Sara Wijayanto uses code-mixing in her three mystical YouTube videos to negotiate identity and establish spiritual authority in front of a digital audience. The study material consisted of three movies totaling 150 minutes in length, which were transcribed and analyzed using Muysken's code-mixing typology to identify linguistic forms and Fairclough's Critical Discourse Analysis to evaluate ideological and social aspects. The study's findings demonstrate that English vocabulary terms such as